All-foreign prisons in the United States, England and Wales, and Norway: Related logics and local expressions - Tuck, Robert Hallam (Theoretical criminology, 2022)
Norway, England and Wales, and the USA are among a small number of affluent Western countries to establish ‘all-foreign’ prisons in response to public concerns about the growing threat of foreign-national prisoners. Drawing on collaborative analysis of empirical data collected at all-foreign prisons in these three countries, this article traces the conditions in which all-foreign prisons emerged, the position and function of all-foreign prisons in specific national systems of criminal justice and immigration control, and the operation of all-foreign prisons within each context. The article points to a shared logic, while drawing attention to the local expressions of bordered penality.